SiOC modified boron carbide-aluminum oxide composite material and preparation method thereof

Through SiOC modification technology, SiOC precursor wrapped in the surface and pores of boron carbide-alumina material, forming SiOC-modified boron carbide-alumina composite material, solving the problem of strong hygroscopicity of the material and improving the anti-hygroscopicity and stability , reducing usage and storage costs.

CN119430987AActive Publication Date: 2025-02-14SHANGHAI INST OF CERAMIC CHEM & TECH CHINESE ACAD OF SCI

Patent Information

Application Number
CN202411671858.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-21
Publication Date
2025-02-14
Estimated Expiration
2044-11-21

AI Technical Summary

Technical Problem

The existing boron carbide-alumina materials have problems such as strong hygroscopicity and high surfactivity, which leads to strict storage and use environments and may burn or pulverize under accident conditions, affecting the safe operation of the nuclear reactor.

Method used

Using SiOC modification technology, SiOC modified boron carbide-alumina composite material is formed by encapsulating the precursor of SiOC in the surface and pores of boron carbide-alumina material, and drying and pyrolyzing.

Benefits of technology

It effectively inhibits the hygroscopicity of boron carbide-alumina material, improves its hygroscopic properties and chemical thermal stability, simplifies the drying and storage conditions before installation of pipes, and reduces the use and storage costs of materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119430987A_ABST
    Figure CN119430987A_ABST
Patent Text Reader

Abstract

The invention relates to a SiOC modified boron carbide-aluminum oxide composite material and a preparation method thereof. The SiOC modified boron carbide-aluminum oxide composite material comprises a porous structure boron carbide-aluminum oxide material and a SiOC layer coating and modifying the porous structure of the boron carbide-aluminum oxide material and the surfaces of boron carbide and aluminum oxide particles, the porosity of the boron carbide-aluminum oxide material with the porous structure is 20 to 40 percent.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of discrete burnable poison components and neutron shielding materials for nuclear reactors, and in particular relates to a SiOC-modified boron carbide-aluminum oxide composite material and a preparation method thereof. Background Art

[0002] Boron carbide (B4C) is a widely used nuclear reactor control rod material. Boron is used as a neutron-absorbing nuclide to adjust the reactor power. Boron carbide releases helium after absorbing neutrons. Ceramic-based neutron-absorbing materials containing boron carbide generally have certain pores to accommodate the release of helium to avoid severe swelling or even disintegration of the material. Boron carbide as a neutron-absorbing material has the advantages of low residual radioactivity after irradiation, low cost, and easy processing. However, it has poor antioxidant properties and is easy to deteriorate when stored in the air for a long time, especially for porous structures. Boron carbide may also burn or pulverize when exposed to oxygen under accident conditions.

[0003] Pellets made of boron carbide-alumina composite materials are also used as wet annular burnable poisons (WABA). Boron carbide-alumina composite materials use alumina as the matrix material and boron carbide as a neutron absorber to improve the oxidation resistance. At the same time, alumina has the characteristics of small neutron absorption cross section, stable physical and chemical properties, and low cost. However, conventional technical means have not yet solved the problem of hygroscopicity of boron carbide-alumina pellets. Due to the strong hygroscopicity of alumina itself and the porous structure of boron carbide-alumina, the material has strong hygroscopicity. Excessive moisture as a source of hydrogen will cause hydrogen embrittlement damage of the zirconium cladding, and the material will dissolve into the moderator medium, seriously affecting the safe operation of the nuclear reactor. Although the earlier discrete burnable poison borosilicate glass design has a lower manufacturing cost, it is impossible to use zirconium alloy cladding because of its high water absorption. Therefore, solving the hygroscopicity problem of boron carbide-alumina pellets is crucial to the safety of zirconium alloy cladding tubes and even the safe operation of nuclear reactions.

[0004] In addition, there are impurities such as free boron and soluble boron on the surface of boron carbide particles. At the same time, during the high-temperature sintering process, boron will volatilize and deposit on the surface of alumina. In an oxygen-rich and high-humidity environment, a variety of chemical reactions will occur on these surfaces, and the generated boric acid will further increase the hygroscopicity. These problems will complicate the material production process, increase the processing links and use costs, and limit the application of boron carbide-alumina pellets. Existing technologies have not proposed corresponding solutions to limit or improve the risk of increased hygroscopicity of boron carbide. Summary of the invention

[0005] In view of the shortcomings and defects in the above-mentioned existing boron carbide-alumina material preparation technology, the present invention proposes a SiOC modified boron carbide-alumina composite material and a preparation method thereof. The method first uses boron carbide powder, alumina powder and a sintering aid to form and sinter to prepare a porous boron carbide-alumina material, and then uses a SiOC precursor to wrap the boron carbide-alumina, and then dries and pyrolyzes to obtain a SiOC modified boron carbide-alumina composite structure. The preparation method can inhibit the side reaction of the boron carbide-alumina surface, improve the moisture absorption resistance, and has a simple process, relatively low cost, and is easy to prepare in batches. The material can be used as a discrete combustible poison for reactor fuel consumption and power control and neutron shielding.

[0006] In a first aspect, the present invention provides a SiOC-modified boron carbide-alumina composite material, wherein the SiOC-modified boron carbide-alumina composite material comprises: a porous boron carbide-alumina material, and a SiOC layer coated and modified on the porous structure of the boron carbide-alumina material and the surface of the boron carbide and alumina particles; The porosity of the porous boron carbide-aluminum oxide material is 20-40%.

[0007] Preferably, the thickness of the SiOC layer modified on the surface of the boron carbide-aluminum oxide material is 1-10 nm, preferably 2-5 nm.

[0008] Preferably, after the SiOC modified boron carbide-aluminum oxide composite material absorbs water for 12-72 hours under the conditions of relative humidity of 80-90% and temperature of 20-30° C., the hydrogen content is 15-30 ppm.

[0009] In a second aspect, the present invention provides a method for preparing the above-mentioned SiOC modified boron carbide-aluminum oxide composite material, the preparation method comprising the following steps: (1) mixing raw material powders containing boron carbide powder, alumina powder, and a sintering aid and forming them into a green billet, and sintering them to obtain a porous boron carbide-alumina material; (2) introducing a SiOC precursor into the pores and surface of the porous boron carbide-alumina material, and drying and encapsulating the material to obtain a boron carbide-alumina composite structure encapsulated by the SiOC precursor; (3) Pyrolyzing the boron carbide-alumina composite structure wrapped by the SiOC precursor to obtain the SiOC-modified boron carbide-alumina composite material.

[0010] Preferably, in step (1), the sintering aid comprises SiO x (x=0-2), at least one of MgO and CaO.

[0011] Preferably, in step (1), the mass ratio of boron carbide powder in the raw material powder is 5-50wt%, preferably 10-40wt%, more preferably 12-20wt%; the mass ratio of alumina powder is 49-94.9%; and the mass ratio of sintering aid is 0.1-1%.

[0012] Preferably, in step (1), the sintering atmosphere is an inert atmosphere or a vacuum environment, and the inert gas is preferably at least one of argon, nitrogen, helium, and carbon dioxide; the sintering temperature is 1400-1700° C., and the sintering time is 1-6 hours.

[0013] Preferably, in step (2), the SiOC precursor comprises at least one of polysiloxane, polysilsesquioxane and silicone resin; and the process of introducing the SiOC precursor comprises dipping, stirring, filtration and spraying.

[0014] Preferably, in step (2), the drying and packaging is carried out in an air atmosphere, the drying and packaging temperature is 60-250° C., preferably 100-200° C., and the drying and packaging time is 1-10 h.

[0015] Preferably, in step (3), the pyrolysis is carried out in an argon or nitrogen atmosphere or under vacuum conditions; the pyrolysis temperature is 900-1200° C., and the pyrolysis time is 1-5 hours.

[0016] Beneficial Effects (1) The present invention improves the defects of boron carbide-alumina boron carbide-alumina materials, such as strong hygroscopicity, high surface activity, and strict requirements on storage and use environment. The SiOC-modified boron carbide-alumina boron carbide-alumina composite structure prepared by the present invention effectively improves the hygroscopic properties of porous boron carbide-alumina boron carbide-alumina materials; (2) The SiOC-modified boron carbide-alumina boron carbide-alumina material of the present invention is coated on the surface of boron carbide-alumina boron carbide-alumina with a precursor containing Si, O, and C such as polysiloxane, polysilsesquioxane, and silicone resin, and the SiOC-modified boron carbide-alumina boron carbide-alumina material is obtained by drying and pyrolysis, and the surface properties with excellent chemical and thermal stability can be obtained; (3) The SiOC used in the present invention can be evenly distributed in the porous structure of boron carbide-alumina boron carbide-alumina, preventing the hydrophilic alumina from absorbing water vapor in the environment, and also inhibiting the generation, diffusion and adsorption of water vapor of boric acid, free boron, etc. on the surface of boron carbide particles; (4) The SiOC precursor used in the present invention is low-cost, does not produce harmful substances, is environmentally friendly, and the preparation method of the modified boron carbide-alumina boron carbide-alumina material is simple in process, can process boron carbide-alumina materials of any shape, and is easy to achieve large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 A schematic diagram of the microstructure of an exemplary SiOC-modified boron carbide-aluminum oxide composite material provided by the present invention; Figure 2 This is a sample image before pyrolysis in Example 2; Figure 3 This is a sample image after pyrolysis in Example 3; Figure 4 This is the XRD pattern of the SiOC modified boron carbide-aluminum oxide composite material prepared in Example 4; Reference numerals: 1. Boron carbide particles; 2. Aluminum oxide particles; 3. SiOC layer; 4. Pores. DETAILED DESCRIPTION

[0018] The present invention is further described below by the following embodiments. It should be understood that the following embodiments are only used to illustrate the present invention, but not to limit the present invention.

[0019] First, if Figure 1 As shown, the present invention provides a SiOC modified boron carbide-alumina composite material. The SiOC modified boron carbide-alumina composite material comprises: a porous boron carbide-alumina material, and a SiOC layer coated and modified on the porous structure of the boron carbide-alumina material and the surface of the boron carbide and alumina particles.

[0020] Boric acid, boron oxide, Al2O3 and other substances are formed on the surface and interface of the boron carbide-alumina pellet during the sintering process. 18 B4O 33 and other components that are easy to absorb water. Silicon oxygen carbon (SiOC) is a precursor conversion ceramic with the advantages of high thermal stability, oxidation resistance, high strength, etc. It can be used as a high-temperature structural material, functional material, and structural absorbing material, etc. The SiOC used in the present invention can be evenly distributed on the porous structure and surface of boron carbide-alumina. By introducing SiOC to modify the surface of the particles, a hydrophobic protective layer is formed to inhibit the adsorption of water molecules, and prevent the highly hydrophilic alumina from absorbing water vapor in the environment. At the same time, the generation, diffusion, and adsorption of water vapor of boric acid, free boron, etc. on the surface of the boron carbide particles are inhibited. Furthermore, the SiOC-modified boron carbide-alumina provided by the present invention can improve the anti-water absorption performance by utilizing the inorganic components (such as SiO2, SiC, C, etc.) formed after the cracking of SiOC precursors such as organic silicon.

[0021] In some embodiments, the porosity of the porous boron carbide-alumina material may be 20-40%, and the pore size may be 0.1-2 μm. If the porosity is too low, it will be difficult for the SiOC precursor to enter the pores and contact the boron carbide or alumina particles during the preparation process; if the porosity is too high, the material has poor anti-hygroscopic performance.

[0022] In some embodiments, the thickness of the SiOC layer modified on the surface of the boron carbide-aluminum oxide material can be 1-10 nm, preferably 2-5 nm. If the SiOC layer is too thick, the content of impurity elements such as C and Si will be too high; if the SiOC layer is too thin, it will not be able to isolate moisture.

[0023] In some embodiments, after the SiOC modified boron carbide-aluminum oxide composite material absorbs water for 12-72 hours under the conditions of relative humidity of 80-90% and temperature of 20-30° C., the hydrogen content is 15-30 ppm.

[0024] The following is an exemplary description of the preparation method of the SiOC modified boron carbide-aluminum oxide composite material provided by the present invention. The preparation method may include the following steps: (1) mixing raw material powders containing boron carbide powder, alumina powder, and a sintering aid and forming them into a green billet, and sintering them to obtain a porous boron carbide-alumina material; (2) introducing a SiOC precursor into the pores and surface of the porous boron carbide-alumina material, and drying and encapsulating the material to obtain a boron carbide-alumina composite structure encapsulated by the SiOC precursor; (3) Pyrolyzing the boron carbide-alumina composite structure wrapped by the SiOC precursor to obtain the SiOC-modified boron carbide-alumina composite material.

[0025] In some embodiments, in step (1), the particle size of the boron carbide powder can be 2-50 μm, and the D50 of the alumina powder particle size can be 50-500 nm, preferably 100-200 nm. If the boron carbide particles are too large, the neutron absorption performance will be weakened due to the self-shielding effect; if the size is too small, it will cause rapid swelling, stronger water absorption, and inhibit the sintering densification of alumina in the material. Moreover, the smaller the boron carbide particles and the higher the content, the more difficult it is for alumina-boron carbide to achieve densification, and a higher sintering temperature is required.

[0026] In some embodiments, in step (1), the sintering aid may include SiO x (x=0-2), at least one of MgO and CaO; preferably, the powder particle size of the sintering aid can be 20-100nm.

[0027] In some embodiments, in step (1), the mass ratio of boron carbide powder in the raw material powder can be 5-50wt%, preferably 10-40wt%, more preferably 12-20wt%, the mass ratio of alumina powder can be 49-94.9%, and the mass ratio of sintering aid can be 0.1-1%.

[0028] The function and structure of the material can be guaranteed by controlling the appropriate raw material ratio. If the boron carbide content is too high, the water absorption will become stronger, and if the content is too low, the set neutron absorption function cannot be exerted. Alumina acts as a matrix, which can form a porous structure to accommodate helium release and swelling. If the alumina content is too low, it is easy to cause the material structure to collapse and damage in the middle and late stages of its service life (18-24 months).

[0029] In some embodiments, in step (1), the sintering atmosphere can be an inert atmosphere or a vacuum environment, and preferably the inert gas can be at least one of argon, nitrogen, helium, and carbon dioxide; the sintering temperature can be 1400-1700°C, and the sintering time can be 1-6h.

[0030] In some embodiments, in step (2), the SiOC precursor may include at least one of polysiloxane, polysilsesquioxane, and silicone resin.

[0031] It should be noted that directly mixing SiOC with the raw materials easily forms an independent third phase, but cannot achieve the purpose of in-situ modification on the surface of the porous boron carbide-alumina material. By introducing a liquid precursor, the porous boron carbide-alumina material can be uniformly coated, and the process is simple, and the purpose of modification can be achieved through a simple pyrolysis process.

[0032] In some embodiments, in step (2), the process of introducing the SiOC precursor may include dipping, stirring, filtration, and spraying, wherein the number of dipping may be 1 to 5 times.

[0033] In some embodiments, in step (2), the dry wrapping can be carried out in an air atmosphere, the dry wrapping temperature can be 60-250°C, preferably 100-200°C, and the dry wrapping time can be 1-10 hours. The number of dry wrapping can be 1-5 times. If the temperature is too low and the time is too short, the moisture and solvent in the core block wrapped by the precursor cannot be completely removed, and the initial curing cannot be completed, which affects the uniformity of the wrapping layer and the high-temperature pyrolysis, and the effect of improving the anti-water absorption performance is not good.

[0034] In some embodiments, in step (3), the pyrolysis can be performed under flowing argon, nitrogen atmosphere or vacuum conditions; the pyrolysis temperature can be 900-1200°C, and the pyrolysis time can be 1-5 hours. If the pyrolysis temperature is too low, the precursor cannot be completely cracked; if the pyrolysis temperature is too high, too much SiC will be generated and the product particles will be too large.

[0035] The SiOC modified boron carbide-alumina composite material provided by the present invention can significantly improve the anti-hygroscopic performance of boron carbide-alumina when used as a discrete combustible poison, simplify the drying and storage conditions before pipe filling, and reduce the use and storage costs of the material.

[0036] The following further examples are given to illustrate the present invention in detail. It should also be understood that the following examples are only used to further illustrate the present invention and cannot be construed as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above content of the present invention all belong to the scope of protection of the present invention. The specific process parameters of the following examples are also only examples within a suitable range, that is, those skilled in the art can make selections within a suitable range through the description of this article, and are not limited to the specific values ​​​​exemplified below. If not specifically stated, the technical means used in the embodiments are conventional means well known to those skilled in the art.

[0037] Example 1

[0038] The preparation method of the SiOC modified boron carbide-aluminum oxide composite material provided in this embodiment comprises the following steps: (1) Take 10g of boron carbide powder (5-35μm) and 90g of alumina powder (D50 is 300nm), add 0.2g of magnesium oxide as a sintering aid, then add 500g of water and a binder, mix evenly by ball milling, and spray granulate to obtain a mixed powder; take 2g of the mixed powder and press it to obtain a ring-shaped blank, and sinter the blank in an argon atmosphere furnace at 1500°C for 2 hours to obtain a porous boron carbide-alumina material; (2) preparing a solution containing a SiOC precursor, using polysiloxane as a solute and anhydrous ethanol as a solvent, and preparing a 50% (wt) solution, and using the solution to impregnate the porous boron carbide-alumina material obtained in step (1) for 2 minutes; the impregnated porous boron carbide-alumina material is cross-linked in air at 200° C. for 1 hour and then dried and wrapped to obtain a boron carbide-alumina composite structure wrapped by the SiOC precursor; (3) Pyrolyzing the boron carbide-alumina composite structure wrapped by the SiOC precursor obtained in step (2) in a pyrolysis furnace protected by a nitrogen atmosphere at a pyrolysis temperature of 1000° C. for 1 hour, and cooling to room temperature to obtain a SiOC-modified boron carbide-alumina composite material.

[0039] The test shows that the porosity of the boron carbide-alumina material in the SiOC modified boron carbide-alumina composite material prepared in this embodiment is 30%; after absorbing water in an oven at a relative humidity of 80% and a temperature of 25°C for 48 hours, the hydrogen content (as an indicator for judging water absorption) of the SiOC modified boron carbide-alumina composite material prepared in this embodiment is tested by a nitrogen, oxygen and hydrogen meter and is 18 ppm.

[0040] Example 2

[0041] The preparation method of the SiOC modified boron carbide-alumina composite material provided in this embodiment refers to that in Example 1, the main difference is that: In step (1), 0.5 g of magnesium oxide is used and the sintering temperature of the green body is 1450°C.

[0042] Figure 2 This is a sample picture before pyrolysis in Example 2. As can be seen from the figure, the annular boron carbide-alumina pellet wrapped by the precursor is light gray in color.

[0043] The test shows that the porosity of the boron carbide-alumina material in the SiOC modified boron carbide-alumina composite material prepared in this embodiment is 35%; after absorbing water in an oven at a relative humidity of 80% and a temperature of 25°C for 48 hours, the hydrogen content (as an indicator for judging water absorption) of the SiOC modified boron carbide-alumina composite material prepared in this embodiment is tested by a nitrogen, oxygen and hydrogen meter and is 30 ppm.

[0044] Example 3

[0045] The preparation method of the SiOC modified boron carbide-alumina composite material provided in this embodiment refers to that in Example 1, the main difference is that: In step (2), the concentration of the solution containing the SiOC precursor is 20% (wt).

[0046] Figure 3 This is a sample picture after pyrolysis in Example 3. As can be seen from the picture, the annular boron carbide-alumina pellet is dark gray in color.

[0047] The test shows that the porosity of the boron carbide-alumina material in the SiOC modified boron carbide-alumina composite material prepared in this embodiment is 29%; after absorbing water in an oven at a relative humidity of 80% and a temperature of 25°C for 48 hours, the hydrogen content (as an indicator for judging water absorption) of the SiOC modified boron carbide-alumina composite material prepared in this embodiment is tested by a nitrogen, oxygen and hydrogen meter and is 21 ppm.

[0048] Example 4

[0049] The preparation method of the SiOC modified boron carbide-alumina composite material provided in this embodiment refers to that in Example 1, the main difference is that: In step (1), the sintering aid is silicon oxide, and the added amount is 0.5 g. In step (2), polysilsesquioxane is used as a solute to prepare a 30% (wt) solution; the temperature for drying the package is 150°C.

[0050] Figure 4 This is the XRD pattern of the SiOC modified boron carbide-alumina composite material prepared in Example 4. As can be seen from the figure, boron carbide and alumina are the main diffraction peaks, and the peak intensity of boron carbide is relatively weak.

[0051] The test shows that the porosity of the boron carbide-alumina material in the SiOC modified boron carbide-alumina composite material prepared in this embodiment is 28%; after absorbing water in an oven at a relative humidity of 80% and a temperature of 25°C for 48 hours, the hydrogen content (as an indicator for judging water absorption) of the SiOC modified boron carbide-alumina composite material prepared in this embodiment is tested by a nitrogen, oxygen and hydrogen meter and is 19 ppm.

[0052] Example 5

[0053] The preparation method of the SiOC modified boron carbide-alumina composite material provided in this embodiment refers to that in Example 1, the main difference is that: In step (1), the sintering aid is silicon oxide; In step (2), a solution is prepared using silicone resin as a solute; In step (3), the pyrolysis atmosphere is an argon atmosphere.

[0054] The test shows that the porosity of the boron carbide-alumina material in the SiOC modified boron carbide-alumina composite material prepared in this embodiment is 26%; after absorbing water in an oven at a relative humidity of 80% and a temperature of 25°C for 48 hours, the hydrogen content (as an indicator for judging water absorption) of the SiOC modified boron carbide-alumina composite material prepared in this embodiment is tested by a nitrogen, oxygen and hydrogen meter and is 15 ppm.

[0055] Example 6

[0056] The preparation method of the SiOC modified boron carbide-alumina composite material provided in this embodiment refers to that in Example 1, the main difference is that: In step (1), 20 g of boron carbide powder, 79.8 g of aluminum oxide powder, and 0.2 g of silicon oxide as a sintering aid are used.

[0057] The test shows that the porosity of the boron carbide-alumina material in the SiOC modified boron carbide-alumina composite material prepared in this embodiment is 29%; after absorbing water in an oven at a relative humidity of 80% and a temperature of 25°C for 48 hours, the hydrogen content (as an indicator for judging water absorption) of the SiOC modified boron carbide-alumina composite material prepared in this embodiment is tested by a nitrogen, oxygen and hydrogen meter and is 19 ppm.

[0058] Example 7

[0059] The preparation method of the SiOC modified boron carbide-alumina composite material provided in this embodiment refers to that in Example 1, the main difference is that: In step (1), the sintering aid is silicon oxide, the addition amount is 0.8 g, and the sintering temperature of the green billet is 1600° C. In step (2), the solution is impregnated into the porous structure boron carbide-alumina material for 5 minutes, dried and packaged at 100° C., and the impregnation, drying and packaging process is repeated twice.

[0060] The test shows that the porosity of the boron carbide-alumina material in the SiOC modified boron carbide-alumina composite material prepared in this embodiment is 35%; after absorbing water in an oven at a relative humidity of 80% and a temperature of 25°C for 48 hours, the hydrogen content (as an indicator for judging water absorption) of the SiOC modified boron carbide-alumina composite material prepared in this embodiment is tested by a nitrogen, oxygen and hydrogen meter and is 15 ppm.

[0061] Example 8

[0062] The preparation method of the SiOC modified boron carbide-alumina composite material provided in this embodiment refers to that in Example 1, the main difference is that: In step (1), 15 g of boron carbide powder, 84.5 g of alumina powder, 0.5 g of silicon oxide as a sintering aid, and the green body sintering temperature is 1550° C. In step (2), the temperature of drying the package is 250°C; In step (3), the drying atmosphere is an argon atmosphere and the pyrolysis temperature is 1100°C.

[0063] The test shows that the porosity of the boron carbide-alumina material in the SiOC modified boron carbide-alumina composite material prepared in this embodiment is 32%; after absorbing water in an oven at a relative humidity of 80% and a temperature of 25°C for 48 hours, the hydrogen content (as an indicator for judging water absorption) of the SiOC modified boron carbide-alumina composite material prepared in this embodiment is tested by a nitrogen, oxygen and hydrogen meter and is 21 ppm.

[0064] Comparative Example 1

[0065] The preparation method of the composite material provided in this comparative example refers to Example 3, with the main differences being: The modification of SiOC in steps (2) and (3) was not performed.

[0066] The test shows that after the boron carbide-aluminum oxide composite material prepared in this comparative example absorbs water in an oven at a relative humidity of 80% and a temperature of 25° C. for 48 hours, the hydrogen content (as an indicator for judging water absorption) tested by a nitrogen-oxygen-hydrogen meter is 45 ppm.

[0067] Comparative Example 2

[0068] The preparation method of the composite material provided in this comparative example refers to Example 1, with the main differences being: In step (1), the sintering temperature of the green billet is 1350°C.

[0069] The test shows that after the boron carbide-aluminum oxide composite material prepared in this comparative example absorbs water in an oven at a relative humidity of 80% and a temperature of 25° C. for 48 hours, the hydrogen content (as an indicator for judging water absorption) tested by a nitrogen-oxygen-hydrogen meter is 48 ppm.

[0070] Comparative Example 3

[0071] The preparation method of the composite material provided in this comparative example refers to Example 1, with the main differences being: In step (1), the sintering holding time of the green billet is 0.5 hours, and the porosity of the obtained boron carbide-alumina material is 42%.

[0072] The test shows that after the boron carbide-aluminum oxide composite material prepared in this comparative example absorbs water in an oven at a relative humidity of 80% and a temperature of 25° C. for 48 hours, the hydrogen content (as an indicator for judging water absorption) tested by a nitrogen-oxygen-hydrogen meter is 72 ppm.

[0073] It can be seen from the comparative example that the porosity of the boron carbide-alumina material is too large and its water absorption performance is increased.

[0074] Comparative Example 4

[0075] The preparation method of the composite material provided in this comparative example refers to Example 1, with the main differences being: In step (2), the concentration of the solution containing the SiOC precursor is 80% (wt).

[0076] The test shows that after the boron carbide-aluminum oxide composite material prepared in this comparative example absorbs water in an oven at a relative humidity of 80% and a temperature of 25° C. for 48 hours, the hydrogen content (as an indicator for judging water absorption) tested by a nitrogen-oxygen-hydrogen meter is 32 ppm.

[0077] Too high a concentration of the precursor solution will result in the modified membrane being too thick, uneven, pores being blocked, and the membrane being broken, and its water absorption performance being increased.

[0078] Comparative Example 5

[0079] The preparation method of the composite material provided in this comparative example refers to Example 1, with the main differences being: In step (3), the pyrolysis temperature is 800°C.

[0080] The test shows that after the boron carbide-aluminum oxide composite material prepared in this comparative example absorbs water in an oven at a relative humidity of 80% and a temperature of 25° C. for 48 hours, the hydrogen content (as an indicator for judging water absorption) tested by a nitrogen-oxygen-hydrogen meter is 50 ppm.

[0081] When the pyrolysis temperature is too low, the precursor reaction is incomplete, resulting in increased water absorption of the composite material.

[0082] Although the content of the present invention has been described in detail through the above preferred embodiments, it should be appreciated that the above description should not be considered as a limitation of the present invention. After reading the above content, it will be apparent to those skilled in the art that various modifications and substitutions of the present invention will occur. Therefore, the protection scope of the present invention should be limited by the appended claims.

Claims

1. A SiOC modified boron carbide-aluminum oxide composite material, characterized in that: The SiOC modified boron carbide-alumina composite material comprises: a porous boron carbide-alumina material, and a SiOC layer coated and modified on the porous structure of the boron carbide-alumina material and the surface of the boron carbide and alumina particles; The porosity of the porous boron carbide-aluminum oxide material is 20-40%.

2. The SiOC modified boron carbide-aluminum oxide composite material according to claim 1, characterized in that: The thickness of the SiOC layer modified on the surface of the boron carbide-aluminum oxide material is 1-10 nm, preferably 2-5 nm.

3. The SiOC modified boron carbide-aluminum oxide composite material according to claim 1 or 2, characterized in that: After the SiOC modified boron carbide-aluminum oxide composite material absorbs water for 12-72 hours under the conditions of relative humidity of 80-90% and temperature of 20-30° C., the hydrogen content is 15-30 ppm.

4. A method for preparing the SiOC modified boron carbide-aluminum oxide composite material according to any one of claims 1 to 3, characterized in that: The preparation method comprises the following steps: (1) mixing raw material powders containing boron carbide powder, alumina powder, and a sintering aid and forming them into a green billet, and sintering them to obtain a porous boron carbide-alumina material; (2) introducing a SiOC precursor into the pores and surface of the porous boron carbide-alumina material, and drying and encapsulating the material to obtain a boron carbide-alumina composite structure encapsulated by the SiOC precursor; (3) Pyrolyzing the boron carbide-alumina composite structure wrapped by the SiOC precursor to obtain the SiOC-modified boron carbide-alumina composite material.

5. The preparation method according to claim 4, characterized in that: In step (1), the sintering aid comprises SiO x (x=0-2), at least one of MgO and CaO.

6. The preparation method according to claim 4 or 5, characterized in that: In step (1), the mass ratio of boron carbide powder in the raw material powder is 5-50wt%, preferably 10-40wt%, more preferably 12-20wt%; the mass ratio of alumina powder is 49-94.9%; and the mass ratio of sintering aid is 0.1-1%.

7. The preparation method according to any one of claims 4 to 6, characterized in that: In step (1), the sintering atmosphere is an inert atmosphere or a vacuum environment, and preferably the inert gas is at least one of argon, nitrogen, helium, and carbon dioxide; the sintering temperature is 1400-1700° C., and the sintering time is 1-6 hours.

8. The preparation method according to any one of claims 4 to 7, characterized in that: In step (2), the SiOC precursor includes at least one of polysiloxane, polysilsesquioxane, and silicone resin; and the process of introducing the SiOC precursor includes dipping, stirring, filtration, and spraying.

9. The preparation method according to any one of claims 4 to 8, characterized in that: In step (2), the drying and packaging is carried out in an air atmosphere, the drying and packaging temperature is 60-250° C., preferably 100-200° C., and the drying and packaging time is 1-10 h.

10. The preparation method according to any one of claims 4 to 9, characterized in that: In step (3), the pyrolysis is carried out in an argon or nitrogen atmosphere or under vacuum conditions; the pyrolysis temperature is 900-1200° C., and the pyrolysis time is 1-5 hours.

Citation Information

Patent Citations

  • Application of surface-modified cordierite in realizing soot conversion

    CN105032456A

  • Neutron absorbing material and preparation method thereof

    CN105200274A

  • Method for producing composite material

    JP2013010669A

Cited By

  • Activated aluminum oxide with low wear index and preparation method thereof

    CN122520103A

  • Active alumina with low attrition index and method for producing the same

    CN122520103B